2020
DOI: 10.1097/mao.0000000000002542
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Epidemiology and Management Trends of Vestibular Schwannomas

Abstract: Objective: To determine the current epidemiology and management trends for patients with vestibular schwannomas (VS). Study Design: Retrospective cohort study. Setting: The Surveillance, Epidemiology, and End Results (SEER) tumor registry. Patients: The SEER database was queried to identify patients diagnosed with VS from 1973 to 2015. Demographics, patient and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The goal of VS treatment has shifted from saving lives towards functional preservation, with multifaceted decision including watch-wait-rescan protocol, surgical resection and radiation ( 4 , 5 ). However, surgery can be traumatic ( 6 ), while radiotherapy has a low hearing retention rate and can affect neurological function even after many years ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of VS treatment has shifted from saving lives towards functional preservation, with multifaceted decision including watch-wait-rescan protocol, surgical resection and radiation ( 4 , 5 ). However, surgery can be traumatic ( 6 ), while radiotherapy has a low hearing retention rate and can affect neurological function even after many years ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that conservative management in small‐ to medium‐sized VS (less than 2cm) can improve rates of facial nerve preservation and hearing protection in comparison to patients who undergo primary surgical treatment ( 10 ). Therefore, for stable or involuting tumors with no mass effect, or elderly patients who will suffer higher risk of comorbidities, the continuing trend toward observation with regular follow-up imaging is reasonable ( 5 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vestibular schwannoma (VS), formerly referred to as acoustic neuroma, is one of the common benign intracranial tumors with rising incidence due to improved and more frequent neuroimaging [1][2][3]. These common tumors of the cerebellopontine angle arise from the Schwann cells of vestibulocochlear nerve, and management with main therapeutic modalities of surgery and radiation therapy (RT) may be considered while observation is also an option for selected patients [4][5][6][7][8]. Several studies have also addressed multimodality management of VS to improve the toxicity profi le of treatment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic neuroma (AN), also known as acoustic neurinoma or vestibular schwannoma is a primary intracranial tumor derived from Schwann cells of the myelin sheath surrounding the 8th cranial nerve which may be observed or treated by surgery, radiosurgery, or with a combined modality approach depending on individual patient and tumor characteristics [1][2][3][4][5]. The incidence of these benign and typically slow growing tumors is in an increasing trend given the substantial improvements in neuroimaging techniques and aging of the population [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of these benign and typically slow growing tumors is in an increasing trend given the substantial improvements in neuroimaging techniques and aging of the population [6][7][8]. Despite the indolent disease course in an overwhelming majority of patients, symptomatology may include hearing impairment, tinnitus, vertigo, dizziness, headache, incoordination or instability, gait ataxia, cranial nerve symptoms due to involvement of facial and trigeminal nerves, facial dysesthesia or spasms, dysphagia, dysarthria, cerebellar seizures, symptoms of increased intracranial pressure and respiratory distress in some of the affected patients [1][2][3][4][5]. AN is typically located in the internal auricular canal or at the cerebellopontine angle in the vicinity of critical neurovascular structures, and compression Copyright@ Omer Sager | Biomed J Sci & Tech Res | BJSTR.…”
Section: Introductionmentioning
confidence: 99%